2017
DOI: 10.1016/s2215-0366(17)30135-9
|View full text |Cite|
|
Sign up to set email alerts
|

A blind spot on the global mental health map: a scoping review of 25 years' development of mental health care for people with severe mental illnesses in central and eastern Europe

Abstract: Twenty-five years have passed since the major socio-political changes in Central and Eastern Europe and our aim was to map and analyze the development of mental health care practice for people with severe mental illnesses in this region since then. A scoping review was complemented by an expert survey in 24 countries. Mental health care practice in the region differs greatly across as well as within individual countries. National policies often exist but reforms remain mostly in the realm of aspiration. Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
145
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(162 citation statements)
references
References 26 publications
3
145
0
5
Order By: Relevance
“…Overall, our data regarding the obstacles to ED/EI implementation additionally confirmed that the greatest challenges in mental healthcare in CEE seem to be insufficient resource allocation and non‐transparent decision making (Winkler et al, ). This affects the implementation of novel, advanced methods in psychiatry, including ED/EI services for psychosis in most CEE countries.…”
Section: Discussionsupporting
confidence: 73%
“…Overall, our data regarding the obstacles to ED/EI implementation additionally confirmed that the greatest challenges in mental healthcare in CEE seem to be insufficient resource allocation and non‐transparent decision making (Winkler et al, ). This affects the implementation of novel, advanced methods in psychiatry, including ED/EI services for psychosis in most CEE countries.…”
Section: Discussionsupporting
confidence: 73%
“…17 Despite this, they tend to have high institutional inertia because they are historically rooted. [18][19][20][21][22] Finally, they operate on a high marginal cost per service user-resources that could be better used for community-based services. [23][24][25] Therefore, one of the key tenets of deinstitutionalization is for mental health care to be provided through service outlets accessible to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Culturally-specific stigma studies are still lacking, and most studies on the subject used Western-developed stigma measures or lacked explicit stigma-specific conceptual frameworks (Yang et al, 2014). Evidence from Central and Eastern Europe on stigma is particularly limited, especially on stigma experienced by family members and carers (Evans-Lacko et al, 2014;Winkler et al, 2017).…”
mentioning
confidence: 99%